THE INFLUENCE HUMAN RESOURCES QUALITY, REGIONAL MANAGEMENT INFORMATION SYSTEM IMPLEMENTATION, ROLE EXPLANATION AND MOTIVATION OF LOCAL EXPENDITURE PERFORMANCE IN SERDANG BEDAGAI REGENCY - juniarty, rixtrynitha (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to examine and to analyze the influence of Human Resources Quality, SIMDA (implementation of Regional Management Information System), Clarity of Role, and motivation on the performance of treasurers expenditure of SKPD (Regional Work Unit) in Serdang Bedagai District Administration. The research used associative causality method. The population was 47 respondents from 47 SKPDs. The samples were taken by  using census sampling technique (total population). Primary data were gathered by using questionnaires and analyzed by using Partial Least Square (PLS) program. The result of the research showed that partially Human Resources Quality, SIMDA (implementation of Regional Management Information), Clarity of Role, and motivation had positive and significant influence on the performance of treasurers expenditure of SKPDs in Serdang Bedagai District Administration.